KONSTRUKSI MAKNA JURU PARKIR WANITA DI KOTA PEKANBARU - Nova Rafika Putri; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Parking attendant as a profession that is generally dominated by men now also in demand by women. This profession become a choice because it is considered as an easy profession but producing. Until this time, in some corner of the city of Pekanbaru are found many women working as parking attendant. This study aims to determine the motive, meaning, and communication experiences of womenparking attendant in Pekanbaru.This study uses qualitative research with phenomenological approach. The subject of research is consistof sixwomenparking attendants who has been chosen using by the purposive technique. This study used data collection techniques observation, depth interviews, and documentation of research. To achieve thevalidity of the datathis study, researcher usedthe extension ofparticipationandtriangulation.The results showedfirstly, motive woman working as parking attendant consists of because motive that is in the form of economic demands, age factor, low education, there is a chance becoming parking attendant, and compulsion. While in order to motiveis stop becoming a parking attendant and stay to be a parking attendant. Secondly, the meaning of parking attendant by women parking attendant are parking attendant as a decent job, parking attendant as the fields of sustenance, and parking attendant is not women's job.Thirdly, communication experience categorized into two pleasant communication experience in the form of vehicle owners pay more parking fees,getting praise from others, getting the support from the family, and getting the support fromthe owner of the shop. While the unpleasant communication experiences in the form of responses and bad view of society, the vehicle owner who berated a woman parking attendant, the vehicle owner does not pay parking fees on vehicles, getting interference from thugs, and no support from the family.Keywords : meaning construction, woman parking attendants, motive , communication experience